2015
DOI: 10.1097/mcc.0000000000000205
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic and ventilator management in patients following cardiac arrest

Abstract: Purpose of review The purpose of this study is to review the recent literature describing how to assess and treat postcardiac arrest syndrome associated haemodynamics and manage oxygenation and ventilation derangements. Recent findings Postcardiac arrest syndrome is a well described entity that includes systemic ischemia-reperfusion response, myocardial dysfunction and neurologic dysfunction. Continued resuscitation in the hours to days following return of spontaneous circulation (ROSC) is important to incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 45 publications
0
8
0
2
Order By: Relevance
“…In our study, patients who suffered a cardiac arrest but had a perfusing rhythm at the time of ETI were included. Peri-cardiac arrest hypotension due to myocardial dysfunction is common and leads to poor outcomes [28,29]. In addition, data from Get-With-The-Guidelines registry has demonstrated that hypotension surrounding an acute respiratory compromise event is frequently associated with cardiac arrest [30].…”
Section: Clinical Utility Of Hyps and (S) Hypsmentioning
confidence: 99%
“…In our study, patients who suffered a cardiac arrest but had a perfusing rhythm at the time of ETI were included. Peri-cardiac arrest hypotension due to myocardial dysfunction is common and leads to poor outcomes [28,29]. In addition, data from Get-With-The-Guidelines registry has demonstrated that hypotension surrounding an acute respiratory compromise event is frequently associated with cardiac arrest [30].…”
Section: Clinical Utility Of Hyps and (S) Hypsmentioning
confidence: 99%
“…46 The ideal blood pressure target after cardiac arrest is uncertain, but hypotension after ROSC is clearly associated with worse outcomes. 42 The 2020 AHA guidelines recommended individualized systolic blood pressure and MAP goals given the many factors to consider post-cardiac arrest. 47 However, rapidly restoring MAP > 65 mm Hg or systolic blood pressure > 90 mm Hg is recommended given that MAPs <65 mm Hg are associated with impaired cerebral oximetry and poor outcomes.…”
Section: Hemodynamic Managementmentioning
confidence: 99%
“…However, how hyper-and hypoxemia affect survival and neurological outcomes is controversial. 32,33,42 A recent meta-analysis, which pooled the data of the only 2 clinical studies present in the literature, 34,35 concluded that whereas hyperoxemia in the postarrest period is associated with a worse outcome, during CPR it appears to be related to a higher rate of return of spontaneous circulation. 36 The effects induced by hyperoxemia seem to correlate with the timing of the pathological process, rather than a simple on/off effect.…”
Section: F Iomentioning
confidence: 99%